Gastric tumour-derived ANGPT2 regulation by DARPP-32 promotes angiogenesis. Issue 6 (16th March 2015) - Chen, Zheng; Zhu, Shoumin; Hong, Jun; Soutto, Mohammed; Peng, DunFa; Belkhiri, Abbes; Xu, Zekuan; El-Rifai, Wael
Abstract : Objective: Overexpression of dopamine and cAMP-regulated phosphoprotein, Mr 32000 (DARPP-32), and its truncated isoform (t-DARPP) are associated with gastric tumorigenesis. Herein, we investigated the role of DARPP-32 proteins in regulating angiopoietin 2 (ANGPT2) and promoting tumour angiogenesis. Design: Quantitative real-time RT-PCR, immunoblotting, luciferase reporter, immunofluorescence, immunohistochemistry and angiogenesis assays were applied to investigate the regulation of angiogenesis by DARPP-32 proteins. Results: Overexpression of DARPP-32 significantly increased the mRNA and protein levels of ANGPT2 in gastric cancer cells. The overexpression of DARPP-32 T34A mutant or the N-terminal truncated isoform, t-DARPP, led to similar effects ruling out the T34-dependent regulation of protein phosphatase 1 activity in regulating ANGPT2. DARPP-32 proteins induced a secreted form of ANGPT2, which was detectable in the media, functionally active, and able to induce angiogenesis, measured by the human umbilical vein endothelial cells tube formation assay. Antibody blocking of the secreted ANGPT2 abrogated its function. To identify the mechanism by which DARPP-32 regulates ANGPT2, we examined the activities of NF-κB and signal transducer and activator of transcription 3 (STAT3), known regulators of angiogenesis. The results ruled out NF-κB and showed induction of STAT3 phosphorylation, activation and nuclear localisation. Inhibition or knockdown of STAT3 significantly attenuated the induction of ANGPT2 by DARPP-32 proteins. In vivo xenograft models demonstrated that overexpression of DARPP-32 promotes angiogenesis and tumour growth. Analyses of human gastric cancer tissues showed a strong correlation between DARPP-32 and ANGPT2. Conclusions: Our novel findings establish the role of DARPP-32-STAT3 axis in regulating ANGPT2 in cancer cells to promote angiogenesis and tumorigenesis.